Captura/separación de hidrógeno en la producción de radioisótopos. - Milidoni, Mauro L. (Comisión Nacional de Energía Atómica. Instituto Balseiro, 2012)
Fil. Milidoni, Mauro L.. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina